G. GIOVANNONI - Tuscany Beyond Tuscany. Rethinking the City from the Periphery - Amoroso, Serafina (ZARCH, 2020)
Giulio GiovannoniTuscany beyond Tuscany. Rethinking the City from the PeripheryFlorencia: Didapress (Dipartimento di Architettura Università degli Studi di Firenze), colección CTS Critical Tuscan Studies, 2017, 182 págs. Tapa blanda. Idioma: inglés. 30 €.ISBN-10: 8896080932